CFD Analysis of Pressure Losses and Deposition Velocities in Horizontal Annuli. (3rd February 2019) - Sultan, Rasel A.; Rahman, Mohammad Azizur; Rushd, Sayeed; Zendehboudi, Sohrab; Kelessidis, Vassilios C.
Abstract : Estimation of pressure losses and deposition velocities is vital in the hydraulic design of annular drill holes in the petroleum industry. The present study investigates the effects of fluid velocity, fluid type, particle size, particle concentration, drill string rotational speed, and eccentricity on pressure losses and settling conditions using computational fluid dynamics (CFD). Eccentricity of the drill pipe is varied in the range of 0–75%, and it rotates about its own axis at 0–150 rpm. The diameter ratio of the simulated drill hole is 0.56. Experimental data confirmed the validity of current CFD model developed using ANSYS 16.2 platform.